Abnormal screening for gestational diabetes, maternal mood disorder, and preterm birth. (24th October 2013) - Sit, Dorothy; Luther, James; (Jesse) Dills, John Louis; Eng, Heather; Wisniewski, Stephen; Wisner, Katherine L
<x xml:space="preserve">Abstract</x> Objective Gestational diabetes mellitus (GDM) affects 7% of pregnant mothers, and those with GDM have increased rates of perinatal complications. Major depressive disorder (MDD) and its pharmacologic treatments are associated with obesity and adverse pregnancy outcomes. In this prospective study, we investigated the relationship between abnormal GDM screens, maternal mood disorders, and adverse outcomes. Methods We examined mothers with MDD, those with bipolar disorder (BD), and healthy controls (HC) at 20, 30, and 36 weeks of gestation and delivery. We obtained demographic data and pre‐pregnancy body mass index (BMI), and confirmed diagnoses with the Structured Clinical Interview for DSM‐IV. We evaluated smoking, alcohol use, substance use, and medication treatments with the Longitudinal Interval Follow‐up Evaluation interview. Mothers received the one‐hour 50‐g glucose challenge test (GCT) at 26–28 weeks of gestation. Outcome variables were preterm birth, birth weight (BW) and peripartum events. Results We enrolled 62 HC, 50 BD, 41 past MDD, and 39 current MDD mother–infant pairs. Mean GCT levels and the frequency of abnormal GCT (>140 mg/dL) did not differ across groups. Rates of smoking (χ2 = 20.68, df = 3, p < 0.001), substance use (χ2 = 21.76, df = 3, p < 0.001), and pre‐pregnancy obesity [BMI ≥ 30 (χ2 = 9.97, df = 3, p = 0.019)] differed significantly across groups. Mothers with BD received medications associated with weight gain significantly more often than others [13/45 (29%), p < 0.001). After adjusting for group differences, GCT levels were associated significantly with increased odds for preterm birth (odds ratio = 1.29, 95% confidence interval: 1.0–1.7, p = 0.05) and increased perinatal events (beta = 0.11, p = 0.04) but were not associated with BW. Conclusions In mothers with or without mood disorders, having increased GCT levels contributes to a higher likelihood for adverse pregnancy outcomes. Mothers with BD or current MDD can have additional risks for adverse outcomes and may benefit from early referral for high‐risk services and supportive management in pregnancy.